Limitaciones para Finalizar la Tesis: Caso de Estudio - Bayona-Oré, Sussy (2018)
The students mostly complete the studies; however, they do not finish the Thesis an indispensable requirement for obtaining the degree. Thesis development is a complex process and has been denominated multiplicity. A factor that helps a student to successfully complete the thesis is the supervisor performance in the thesis development process. This study explored the issues of students that finished their studies but not thesis. The results of a survey directed to 129 graduated students from a private university located in Peru were sampled. The results show that supervision in process of thesis development, lack of time and financial aspects are issues that influence in finish thesis called All but Thesis syndrome.